2013
DOI: 10.1099/vir.0.051698-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural protein P6 encoded by rice black-streaked dwarf virus is recruited to viral inclusion bodies by binding to the viroplasm matrix protein P9-1

Abstract: Like other members of the family Reoviridae, rice black-streaked dwarf virus (RBSDV, genus Fijivirus) is thought to replicate and assemble within cytoplasmic viral inclusion bodies, commonly called viroplasms. RBSDV P9-1 is the key protein for the formation of viroplasms, but little is known about the other proteins of the viroplasm or the molecular interactions amongst its components. RBSDV non-structural proteins were screened for their association with P9-1 using a co-immunoprecipitation assay. Only P6 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…After COS processing, we identified some defense-related proteins, simultaneously the expression of SRBSDV P9-1 and P5 protein were down-regulated [42,43]. Previous studies have shown that the interaction between P9-1 and P5 were essential proteins that formed viroplasms [44,45]. Our results indicated that COS may decrease the infection ability of SRBSDV.…”
Section: Discussionmentioning
confidence: 83%
“…After COS processing, we identified some defense-related proteins, simultaneously the expression of SRBSDV P9-1 and P5 protein were down-regulated [42,43]. Previous studies have shown that the interaction between P9-1 and P5 were essential proteins that formed viroplasms [44,45]. Our results indicated that COS may decrease the infection ability of SRBSDV.…”
Section: Discussionmentioning
confidence: 83%
“…These viroplasm matrix proteins can act as the targets for antiviral molecule screening (106). Other viral nonstructural and structural components are then recruited to viroplasm matrices for genome replication and progeny virion assembly (18,19,46,61,68,99,105). Currently, whether the insect components are involved in the formation of viroplasms is unknown.…”
Section: Viral Multiplicationmentioning
confidence: 98%
“…The functions of only a few of these viral proteins have been studied. P5‐1, P6, and P9‐1 proteins together constitute the viroplasm inclusion (Akita et al, ; L. Sun, Xie, Andika, Tan, & Chen, ; Q. Wang et al, ), which is the site of viral replication and assembly. S7‐1 encodes a tubular protein and is localized in the PD of plant cells (Isogai, Uyeda, & Lee, ; Z.…”
Section: Introductionmentioning
confidence: 99%
“…P5-1, P6, and P9-1 proteins together constitute the viroplasm inclusion (Akita et al, 2012;L. Sun, Xie, Andika, Tan, & Chen, 2013;Q.…”
mentioning
confidence: 99%